Reconstructing Criminality in Latin America - Aguirre, Carlos A.; Buffington, Robert (Rowman & Littlefield Publishers, 2001)
The only reader currently available on criminality in Latin America, Reconstructing Criminality in Latin America reconstructs the way in which different Latin American societies have viewed, described, defined, and reacted to criminal behavior. Crime in Latin America is explored in terms of gender, race, class, and criminological theory. The highly readable essays in this book explore how Catholic notions of sin, natural law, the "divine" rights of absolutist monarchs, liberal rights of "man," positivism, and social Darwinism received a sympathetic, even enthusiastic, endorsement from policy makers throughout Latin America.Reconstructing Criminality in Latin America also shows how new methodologies have given scholars deeper insight into the significance of crime in Latin American societies. The selections testify that the insights of scholars like Eric Hobsbawm and Michel Foucault are the foundations of modern histories of crime in Latin America. This book is ideal for criminal justice, sociology, and Latin American social history courses.